Nano influencer di Instagram sebagai Alternatif Medium Promosi Toko Buku di Yogyakarta - Pandanwangi, Brilindra; Laksani, Hening (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2024)
Promotional media via the internet has altered perceptions and created a challenge for businesses to make prominent advertisements. Consequently, innovative promotional designs are required to attract the target audience and ensure the messages conveyed are seen, heard, and read. The main point is that the more promotional alternatives are available, the less effective they will be. In this matter, consumers bombarded by promotional information tend to avoid it. The promotion strategy using nano influencers based on interpersonal relationships is effective because the messages are intended to influence attitudes and instill trust in others. Nano influencers are different from other types of promotional media because of their capacity to elicit emotional responses. The descriptive qualitative research method is used to examine respondents who have reasons and motivations for purchasing books after seeing nano influencer posts on Instagram. According to information obtained from 100 Yogyakarta respondents, 75,8% of book readers in Yogyakarta have purchased books after being influenced by nano influencer posts on Instagram. The research concluded that the internet approach through nano influencers for alternative promotional media in Yogyakarta is impactful because nano influencer posts can attract attention and create an understanding of a product.